Pemberdayaan Masyarakat Melalui Pola Kemitraan A-B-G di Desa Barusari Dan Desa Padaasih Kecamatan Pasirwangi Kabupaten Garut - Okke Rosmaladewi (LPPM UNINUS, 2012)
The inadequacy of knowledge, skills and purchasing power particularly farmers in the sub-district of Pasirwangi Garut has turned them into the cycle of poverty. It has been abundant of community empowerment program aimed to help the poor to pop off the conflicts and cost a lot already, but many programs are not suitable with the community needs, it is not fit with the purpose and outlying targets. This happens because the empowerment program is parsia, it does not build a system and usually given through temporarily donations, thus it caused the farmers depended on other parties but still powerless. Empowering communities via partnership of ‘A-B-G’ is one of the alternatives and considered better because it has more comprehensive systemic suppoted by every stakeholders participation in order the alleviation of poverty that might be directly perceived its benefits for the community because it fits their needs. The program is also sustainable, especially in encouraging the on-going social transformation from poor to empowered, independent, and eventually becoming a civil society.